Faktor Risiko dan Potensi Penularan Tuberkulosis Paru di Kabupaten Kendal , Jawa Tengah - Wulandari, Agustina Ayu; Nurjazuli, Nurjazuli; Adi, M. Sakundarno (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2015)
Background:Pulmonary tuberculosis (pulmonary TB) is an infectious disease that continues to increase and was a global problem, the number of new cases findings in Kendal showed a rising trend. The prevalence of TB has fluctuated and is likely to increaseby 124 per100,000 populationin 2013. Environmental and behavioral risk factors were factors closely associated with pulmonary TB transmission. One patient with pulmonary TB BTA(+) has the potential to infect other people. This study aimed to know risk factors and the potential forpulmonary tuberculosis transmission to family members. Methods: It was an observational using case control and cross-sectional desing. The subjects ofthis study was 130 people consisted of 65 cases and 65 controls. Data analysis using chi square test and binary logistic regression. Results: Results of sputum examination in contactracing as many as 65 people were successfully retrieved from 44 cases of research, the results showed that there are 3 smear positive(4.6%) and 62 negative smear (95.4%). Risk factors that affect the incidence of lung tuberculosis is residential densityp=0.002, OR=7.841, CI=2.126 to 28.920, room temperature p=0.001, OR=8.048, CI=2.279 to 28.424, p=0.018 indoor humidity, OR=4.705, CI=1.310 to 16.894, the type of house floorp=0.016, OR=5.266, CI=1.356 to 20.446, a habit of throwing sputumany placep=0.016, OR=4.402, CI=1.322 to 14.660, habit cough / sneeze without closing them out hp =<0.001, OR=9.137, CI=2.694 to 30.992. Conclusions: This study concluded that residential density, room temperature, indoor humidity, the type of floor of the house, the habit of throwing sputum any place, habit cough / sneeze without covering them out hare risk factor sincidence of pulmonary tuberculosis in district Kendal. Keywords :Risk factors, pulmonary tuberculosis, transmission.